Design-based research as a research methodology in teacher and social education – a scoping review - Lehrmann, Astrid Lasthein; Skovbjerg, Helle Marie; Arnfred, Simone Jessen (EDeR. Educational Design Research, 2022)
As a methodological approach, design-based research (DBR) has been widely applied within research on educational systems. Nevertheless, the question of how DBR is used as a research method in specific educational environments remains. This scoping review focuses on DBR as a research methodology in teacher education and social education. Such a review can productively map a research area and can guide further research within a field. For this scoping review, 27 articles were selected, and the results showed that DBR is used as a research method in teacher education and social education; however, there are differences in how strictly the articles apply the approaches that are found and are well-known as important features within the DBR methodology. The main finding is that although the selected articles outline their research according to DBR, they do not strictly use the methodology in practice. In most studies, participants are considered co-designers, and the research is conducted in iterative cycles. Because these are the fundamental core features of DBR, it would be relevant to suggest a stronger emphasis on the guidelines within the methodology and insist that future research follows these guidelines to remain within the design-based methodology and thereby strengthen the epistemology of the methodology.